2015
DOI: 10.1007/s00125-015-3853-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term cardiovascular outcomes in type 1 diabetic patients after simultaneous pancreas and kidney transplantation compared with living donor kidney transplantation

Abstract: Aims/hypothesis Mortality due to cardiovascular disease (CVD), particularly coronary artery disease (CAD), is high in type 1 diabetic patients with end-stage renal disease (ESRD). We aimed to determine whether normoglycaemia, as achieved by successful simultaneous pancreas and kidney (SPK) transplantation, could improve long-term outcomes compared with living donor kidney-alone (LDK) transplantation. Methods We studied 486 type 1 diabetic patients with ESRD who underwent a first SPK (n = 256) or LDK (n = 230) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 41 publications
6
35
1
1
Order By: Relevance
“…Very few studies have compared progression of diabetic complications following SPK and LDK transplantation, despite the importance of controlling for the effect of kidney transplantation alone, as some improvements may be due to restoration of normal renal function. Nevertheless, one study has compared long‐term cardiovascular mortality following SPK and LDK transplantation, adjusting for cardiovascular comorbidity, and demonstrated a significant reduction in SPK recipients . In contrast, the current study did not show any difference in cardiovascular mortality between the two transplant modalities.…”
Section: Discussioncontrasting
confidence: 84%
“…Very few studies have compared progression of diabetic complications following SPK and LDK transplantation, despite the importance of controlling for the effect of kidney transplantation alone, as some improvements may be due to restoration of normal renal function. Nevertheless, one study has compared long‐term cardiovascular mortality following SPK and LDK transplantation, adjusting for cardiovascular comorbidity, and demonstrated a significant reduction in SPK recipients . In contrast, the current study did not show any difference in cardiovascular mortality between the two transplant modalities.…”
Section: Discussioncontrasting
confidence: 84%
“…Pancreas transplantation is the optimal treatment for achieving euglycaemia in selected patients with diabetes; it frees patients from the need to administer exogenous insulin, reduces metabolic instability, improves quality of life and may stabilize and reduce the long‐term effects of diabetes . The majority of potential recipients have advanced diabetic nephropathy and are candidates for simultaneous pancreas and kidney transplantation (SPK) .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the ability to maintain normoglycemia after the successful transplant, we believe, contributed to reduced long‐term cardiovascular mortality. Recent studies have shown that diabetic patients treated with SPK patients have lower cardiovascular mortality as compared to even living donor kidney transplant recipients . A successful pancreas transplantation is often able to slow the progression, stabilize, and even reverse many microvascular and macrovascular complications of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…at 5 years) and decreases patient mortality (relative mortality riskRR?, 0.43) . For patients with DM and end‐stage renal disease, SPK significantly improves patient survival compared to dialysis, deceased donor kidney transplantation or even living donor renal transplantation alone …”
Section: Introductionmentioning
confidence: 99%